2022
DOI: 10.3390/cancers14163901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Polyglycolic Acid Mesh Sheet (Neoveil™) in Thyroid Cancer Surgery: A Prospective Randomized Controlled Trial

Abstract: Papillary thyroid cancer (PTC) is the most common type of thyroid cancer. Surgery for PTC involves resection of the thyroid gland and central lymph node dissection. Central lymph node dissection is associated with an increased amount of fluid from the dissection area and chyle leakage due to thoracic duct injury. There are few studies that deal with reducing fluid drainage and preventing chyle leakage after thyroid surgery with central lymph node dissection. A polyglycolic acid mesh sheet (Neoveil™) has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…In terms of the safety of this method, we did not experience any complications specific to this method. Indeed, other studies that apply Neoveil postoperative have not shown any specific complications 16,17–19,23 . One thing to note is that in the early postoperative period, the radiological findings of CT scans performed for surveillance tended to show a “soft tissue density enveloping the hepatic artery”, mimicking recurrence.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In terms of the safety of this method, we did not experience any complications specific to this method. Indeed, other studies that apply Neoveil postoperative have not shown any specific complications 16,17–19,23 . One thing to note is that in the early postoperative period, the radiological findings of CT scans performed for surveillance tended to show a “soft tissue density enveloping the hepatic artery”, mimicking recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Neoveil is a polyglycolic acid sheet that was developed to prevent air and fluid leak from surgical anastomoses. It is widely used in various fields of surgery and has proven to be effective in preventing pulmonary air leak after lung surgery, chyle leakage after thyroid surgery, and anastomosis leakage after distal gastrectomy 17–19 . Neoveil is also being actively utilized in pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is designed to offer additional strength, support tissue regeneration and healing, and potentially reduce the risk of complications. The sheet gradually degrades through hydrolysis before being fully absorbed and metabolized by the body [17].…”
Section: Polyglycolic Acid Sheetmentioning
confidence: 99%